The activities of accounts department Eastcompeace Smart Card (Bangladesh) Ltd. (ECPB) - Habib, Md.Ahsan (BRAC University, 2017)
This internship report is submitted in a partial fulfillment of the requirements for the degree of Master of Business Administration, 2016.